Delivery Mechanisms and Microenterprises Performance: An Analysis of Microcredit Program - Rosman Mahmood; Ahmad Suffian Mohd Zahari (Ital Publication, 2021)
Purpose: The process of identifying and defining effective delivery mechanisms is a critical issue in the management of microcredit programs to meet the firm's objectives and the customers’ needs. The purpose of this paper is to look at the relative importance of delivery mechanism in microcredit programs. In addition, this paper analyses the relationship between delivery mechanism and business performance among micro enterprises involved in microcredit programs. Methodology: The primary data of the study were obtained from 756 micro entrepreneurs under two major microcredit programs (AIM and TEKUN). Descriptive and t-test analysis were used to explain the findings of the study. Findings: Analysis of the study shows that cooperation from staff, the duration and method of loan repayment and monitoring of loan capital are important mechanism in the management of microcredit programs. T-test analysis revealed a significant difference in delivery mechanism between the two microcredit programs involved. Empirical findings show that the performance of micro enterprises under the AIM microcredit program is better than that of micro enterprises under the TEKUN microcredit program. Practical Implications: The performance of a microcredit program depends largely on their resource management. This involves operational efficiency, credit products offered, and customer support services. These three elements are critical factors in determining the effectiveness of the delivery mechanism in a microcredit program. Originality/value:The efficiency of delivery mechanisms through strategic resource management not only can enhance the competitive advantage of the AIM microcredit program but also affect the performance of the micro enterprises involved. Doi: 10.28991/esj-2021-01281 Full Text: PDF